2018
DOI: 10.1183/16000617.0019-2018
|View full text |Cite
|
Sign up to set email alerts
|

The broad spectrum of lung diseases in primary antibody deficiencies

Abstract: Human primary immunodeficiency diseases (PIDs) represent a heterogeneous group of more than 350 disorders. They are rare diseases, but their global incidence is more relevant than generally thought. The underlying defect may involve different branches of the innate and/or adaptive immune response. Thus, the clinical picture may range from severe phenotypes characterised by a broad spectrum of infections to milder infectious phenotypes due to more selective (and frequent) immune defects. Moreover, infections ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 138 publications
(220 reference statements)
5
44
0
2
Order By: Relevance
“…As for PID associated ILD, it has been recognized that PID may be associated with immune-mediated ILD especially in auto-inflammatory disorders, diseases of immune dysregulation, and predominantly antibody deficiencies such as CVID [11][12][13][14][15][16][17][18][19][20]. Two new auto-inflammatory disorders SAVI and COPA syndrome which has been reported to be associated with ILD [15][16][17] were both found in our study cohort.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…As for PID associated ILD, it has been recognized that PID may be associated with immune-mediated ILD especially in auto-inflammatory disorders, diseases of immune dysregulation, and predominantly antibody deficiencies such as CVID [11][12][13][14][15][16][17][18][19][20]. Two new auto-inflammatory disorders SAVI and COPA syndrome which has been reported to be associated with ILD [15][16][17] were both found in our study cohort.…”
Section: Discussionsupporting
confidence: 50%
“…In PID associated ILD, a pathological and HRCT pattern characteristic of lymphocytic intestinal pneumonia (LIP), follicular bronchiolitis (FB), pulmonary nodular lymphoid hyperplasia, and reactive lymphoid infiltrates has been reported and termed "granulomatous-lymphocytic interstitial lung disease (GLILD)" [12,[24][25][26]. GLILD was mainly reported in CVID and has also been reported in other PID such as CTLA4 deficiency, ALPS, lipopolysaccharide responsive beige-like anchor protein (LRBA) deficiency, et al [13,15,20]. In our study cohort, GLILD was found in one CVID patient with characteristic pathological and HRCT findings.…”
Section: Discussionmentioning
confidence: 99%
“…5 Patients with PID are at high risk for viral or bacterial sinopulmonary infections, chronic lung diseases, gastrointestinal diseases, malignancies, and autoimmune disorders. 1,6,7 These conditions may be fatal if left untreated, and early recognition and adequate treatment initiation determine prognosis. 1,6 However, on average, there is a delay of 4e5 years between onset of symptoms and diagnosis, 8e10 and in some cases the delay is up to 9 years.…”
Section: Introductionmentioning
confidence: 99%
“…More than 350 different gene mutations causing immunodeficiency have been described . Bronchiectasis may be the presenting feature of immunodeficiency, or there may have been other clues in the history (Tables ) . An intriguing recent discovery is primary immunodeficiency due to mutations in the P1K3CD gene, causing activated P13K‐δ syndrome (APDS).…”
Section: Causes Of Bronchiectasismentioning
confidence: 99%